Antisepsis Techniques in Orthopedic Surgical Procedures: A Comparative Study - Eugênio César Mendes; Mauro de Castro Carvalho; Rafael Baroni Carvalho; Célio Alves Ferraz; Diba Maria S.T. Souza; Taylor B. Schnaider (Revista Brasileira de Ortopedia)
Abstract Objective To compare antisepsis techniques using chlorhexidine-based soap associated with ethyl alcohol and alcohol-based chlorhexidine or chlorhexidine-based soap associated with alcohol-based chlorhexidine alone in surgical orthopedic procedures. Methods This is a primary, randomized, analytical and single-center clinical trial consisting of 170 patients, who were divided into 2 groups. The combinations chlorhexidine-based soap + alcohol-based chlorhexidine (CSAC) and chlorhexidine-based soap + 70% ethyl alcohol + alcohol-based chlorhexidine (CSAAC) were tested in each group. The cultures were grown in mannitol and eosin methylene blue (EMB) after collection before skin preparation (time point 0), after skin preparation (time point 1) and at the end of the surgical procedure (time point 2). Results There was no statistically significant difference regarding bacterial growth in mannitol and EMB between the groups at any time point. Moreover, there was no statistical difference between groups and time points regarding the type of bacterial growth in culture media. Conclusion There was no difference between these antisepsis techniques for the prevention of surgical site infection in orthopedic procedures; in addition, a protocol containing measures to prevent infection in such procedures was developed.